Kinerja Manajerial: Peranan Sistem Informasi Akuntansi Manajemen Dan Ketidakpastian Lingkungan - Deli, Leni; Irfan, Irfan (Jurnal Riset AKuntansi dan Bisnis, 2025)
This study aims to identify the influence of management accounting information systems and environmental uncertainty on managerial performance at PT. Bank Sumut Medan. The problems faced are the ineffective implementation of management accounting information systems and the existence of environmental uncertainty that affects managerial performance. Research Objectives: This study aims to analyze the influence of management accounting information systems on managerial performance, as well as analyze the influence of environmental uncertainty on managerial performance at PT. Bank Sumut Medan. Research Methods: The method used in this study is quantitative with an associative approach. Data collection was carried out through questionnaires distributed to 80 respondents consisting of managers and employees at PT. Bank Sumut Medan. Data analysis was carried out using Partial Least Squares (PLS). Research Results: The results show that management accounting information systems have a significant effect on managerial performance with a probability value (p-value) 0.05. However, environmental uncertainty is not able to moderate the influence of management accounting information systems on managerial performance.